POLA PENGASUHAN BERSAMA DALAM PUTUSAN 0334/PDT.G/2019/PA.GDT TENTANG PENYELESAIAN SENGKETA HAK ASUH ANAK DI PENGADILAN AGAMA GEDONG TATAAN - Hi Salasa, Masriah; Muhdar, Muhammad Halman (UAS PRESS, 2025)
This study aims to examine and further analyze the legal reasons that underlie the decision to establish shared parenting as a solution for resolving child custody disputes that were applied by the Gedong Tataan Religious Court judge as stated in his decision number 0334/Pdt.G/2019/ PA.Gdt. Research Results That the context of the parkara which is the object of study in this thesis research stems from the divorce lawsuit and child custody dispute (Haḍānah) filed by